Preliminary Deformational Studies on a Finite Element Model of the Nasal Septum Reveals Key Areas for Septal Realignment and Reconstruction. (15th April 2013) - Liong, Kyrin; Lee, Shu Jin; Lee, Heow Pueh
Abstract : Background . With the current lack of clinically relevant classification methods of septal deviation, computer-generated models are important, as septal cartilage is indistinguishable on current imaging methods, making preoperative planning difficult. Methods . Three-dimensional models of the septum were created from a CT scan, and incremental forces were applied. Results . Regardless of the force direction, with increasing force, the septum first tilts (type I) and then crumples into a C shape (type II) and finally into an S shape (type III). In type I, it is important to address the dislocation in the vomer-ethmoid cartilage junction and vomerine groove, where stress is concentrated. In types II and III, there is intrinsic fracture and shortening of the nasal septum, which may be dislocated off the anterior nasal spine. Surgery aims to relieve the posterior buckling and dislocation, with realignment of the septum to the ANS and possible spreader grafts to buttress the fracture sites. Conclusion . By identifying clinically observable septal deviations and the areas of stress concentration and dislocation, a straighter, more stable septum may be achieved.